If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -10 = -1x + 6 Reorder the terms: -10 + 3x = -1x + 6 Reorder the terms: -10 + 3x = 6 + -1x Solving -10 + 3x = 6 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -10 + 3x + x = 6 + -1x + x Combine like terms: 3x + x = 4x -10 + 4x = 6 + -1x + x Combine like terms: -1x + x = 0 -10 + 4x = 6 + 0 -10 + 4x = 6 Add '10' to each side of the equation. -10 + 10 + 4x = 6 + 10 Combine like terms: -10 + 10 = 0 0 + 4x = 6 + 10 4x = 6 + 10 Combine like terms: 6 + 10 = 16 4x = 16 Divide each side by '4'. x = 4 Simplifying x = 4
| 9/4=18/x | | -3y+9=-7+9ysolve | | 2y+4x+5x-30=360 | | 5y+6x=55 | | 7+5y=1 | | 1/2h8 | | (4/9)^0 | | 3/5x+2=10 | | 3/5+2=10 | | x^2+2x+y^2+10y=15 | | -5-6x=37 | | -5-15x+1=2(2x-1)-x | | 29/12(6) | | y-3=-7/9(18) | | x^2+9x=-9x-81 | | 23569x=10050x | | 8y/11=6/7 | | 10490.2376=4*3.14*r^2 | | 10499.2376=4*3.14*r^2 | | 16/n=21/11 | | 0=2x^2-24x-81 | | 9(1)-3y=15 | | -49=-7/9x | | Y/25=24/15 | | f(3)=9+9-7 | | 1.07x(1.1)x=48 | | 5.5x+2=-15x-3+4y | | 9x-3(1)=15 | | 8+6x-29-5x+19=86+x-15 | | 5y-10=-9-3y-8y | | 3x/7=1/11 | | -5-15y+1=2(7y-16) |